Pengaruh Rasio Likuiditas, Rasio Solvabilitas dan Rasio Profitabilitas Terhadap Harga Saham Pada Perusahaan Properti dan Perumahan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2018 - Lily Sitinjak; Jamaluddin Jamaluddin; Vidarwati Laia (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2020)
The purpose of this study is to find out the influence of liquidity ratio, solvability ratio, and profitability ratio on to stock prices for companies. Then method required is a quantitative method while the qualitative method in the from of speech or witing and the behavior of the people observed. The data needed is secondary dat in the annual financial statements. The analysis required is multiple linear analysis according to the SPSS program.The results showed that liquidity ratio, to the prices partially had significanrice and positive effect, solvability ratio to the stock prices was partially significant and had no positive effect and profitability ratio was partially insignificant and had a positive effect on the stock prices of the property real estate building contruction companies listed on the indonesia stock periode 2013-2018. Keywords : liquidity ratio, solvability ratio, profitability ratio and stock prices.